Impact of Inversion Time for FLAIR Acquisition on the T2-FLAIR Mismatch Detectability for IDH-Mutant, Non-CODEL Astrocytomas - Kinoshita, Manabu; Arita, Hideyuki; Takahashi, Masamichi; Uda, Takehiro; Fukai, Junya; Ishibashi, Kenichi; Kijima, Noriyuki; Hirayama, Ryuichi; Sakai, Mio; Arisawa, Atsuko; Takahashi, Hiroto; Nakanishi, Katsuyuki; et al. (Frontiers in Oncology, 2021)
The current research tested the hypothesis that inversion time (TI) shorter than 2400 ms under 3T for FLAIR can improve the diagnostic accuracy of the T2-FLAIR mismatch sign for identifying IDHmt, non-CODEL astrocytomas. We prepared three different cohorts; 94 MRI from 76 IDHmt, non-CODEL Lower-grade gliomas (LrGGs), 33 MRI from 31 LrGG under the restriction of FLAIR being acquired with TI < 2400 ms for 3T or 2016 ms for 1.5T, and 112 MRI from 112 patients from the TCIA/TCGA dataset for LrGG. The presence or absence of the “T2-FLAIR mismatch sign” was evaluated, and we compared diagnostic accuracies according to TI used for FLAIR acquisition. The T2-FLAIR mismatch sign was more frequently positive when TI was shorter than 2400 ms under 3T for FLAIR acquisition (p = 0.0009, Fisher’s exact test). The T2-FLAIR mismatch sign was positive only for IDHmt, non-CODEL astrocytomas even if we confined the cohort with FLAIR acquired with shorter TI (p = 0.0001, Fisher’s exact test). TCIA/TCGA dataset validated that the sensitivity, specificity, PPV, and NPV of the T2-FLAIR mismatch sign to identify IDHmt, non-CODEL astrocytomas improved from 31%, 90%, 79%, and 51% to 67%, 94%, 92%, and 74%, respectively and the area under the curve of ROC improved from 0.63 to 0.87 when FLAIR was acquired with shorter TI. We revealed that TI for FLAIR impacts the T2-FLAIR mismatch sign's diagnostic accuracy and that FLAIR scanned with TI < 2400 ms in 3T is necessary for LrGG imaging.